A utilização da tecnologia RTK NTRIP: analise da viabilidade do uso para georreferenciamento de imóveis rurais - Ribas, Artur Amaral (Universidade do Vale do Rio dos Sinos, 2014)
The georeferencing of rural areas in Brazil is already a reality, and new technologies supported in the mobile network have been developed to enhance the Global Navigation Satellite System (GNSS). In this context, the use of RTK NTRIP technology is highlighted, which uses the mobile phone network to receive real-time corrections through the internet. The objective of this study was analyze the feasibility of using this technology for geo-referencing of rural properties, and for this analysis surveys with different baseline lengths, were conducted, where the data was compared with data obtained from post processed static tracking. The results showed that the positional changes were within the parameters specified by the 3rd Technical Standard for Georeferencing of Rural properties of the INCRA, but it was found that the range of mobile telephony is the main limiting factor for the implementation of surveys in RTK NTRIP method.
Keywords: RTK; NTRIP; Georreferenciamento de áreas rurais; Georeferencing of rural areas